2010
DOI: 10.2527/jas.2009-2378
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in ultrasonic measurements of body composition during growth in Suffolk ram lambs and evaluation of alternative adjustment strategies for ultrasonic scan data

Abstract: Four equations were used to compare alternative procedures to adjust ultrasonic estimates (y) of backfat thickness (BF) and LM area (LMA) for BW using data from a series of 7 scans on 24 Suffolk ram lambs born in 2007. Equations were linear, linear + quadratic, allometric (y = αBW β ), and allometric + BW (ABW; y = αBW β e γW ). Goodness of fit was very similar between equations over the range of the data. Resulting adjustment equations were tested using 3 serial scans on winter-born Suffolk (n = 150), Hampshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In recent years, several works have been published that clearly show that the RTU technique allows good estimates of the composition of the carcass to be obtained. These studies aimed to predict carcass composition in adult animals (Hopkins et al ., 2007;Teixeira et al ., 2008), market lambs Leeds et al ., 2008;Orman et al ., 2008;Thériault et al ., 2009;Emenheiser et al ., 2010;Orman et al ., 2010) or light carcasses (Ripoll et al ., 2009). Although the results obtained were generally good, attention must be paid to the factors that lead to inaccuracy in the RTU technique when used for small ruminants.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, several works have been published that clearly show that the RTU technique allows good estimates of the composition of the carcass to be obtained. These studies aimed to predict carcass composition in adult animals (Hopkins et al ., 2007;Teixeira et al ., 2008), market lambs Leeds et al ., 2008;Orman et al ., 2008;Thériault et al ., 2009;Emenheiser et al ., 2010;Orman et al ., 2010) or light carcasses (Ripoll et al ., 2009). Although the results obtained were generally good, attention must be paid to the factors that lead to inaccuracy in the RTU technique when used for small ruminants.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
“…Subcutaneous fat depth above the LTL muscle and muscle depth and area are the parameters usually measured in RTU examinations. A large number of studies (McEwan et al ., 1989;Silva et al ., 2006a;Teixeira et al ., 2006;Hopkins et al ., 2007;Silva et al ., 2007a;Leeds et al ., 2008;Teixeira et al ., 2008;Thériault et al ., 2009;Emenheiser et al ., 2010;Orman et al ., 2010) have found a significant correlation ( r > 0.6; P < 0.01) between both fat and muscle RTU measurements and the corresponding carcass measurements in those regions. The placement of the probe at reference points must be correct, since SFD and LTL muscles vary significantly over short distances either cranio-caudally (Delfa et al ., 1991;Silva et al ., 2007a) or medium-laterally (Simm, 1983;Korn et al ., 2005).…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the possibility to distinguish changes over time within individuals, from differences among groups in their baseline levels, allows to exclude some variation within treatment from the error term, and this is exploited to draw more powerful inferences. This kinds of longitudinal approach have been used in animals to detect day‐to‐day growth and body composition differences …”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2006) and Cadavez and Monteiro (2011) used multiple regression equations to predict the composition of Chura, Galega, Bragancana and Suffolk lamb carcasses, using the weight of the warm carcass and the ultrasound parameters (the proportion of subcutaneous fat, the intramuscular fat content, the thickness of subcutaneous fat layer and the bone weight) in order to obtain an objective classification and grading of sheep carcasses. Emenheiser et al (2010) showed the necessity of validating the ultrasound method utilization to determine lamb carcass composition for meat production and showed the advantages of this method. In order to improve the evaluation of the sheep selected for meat production, the purpose of this study was to develop non-linear multiple regression equations to evaluate the amount of carcass meat and the amount of selected cuts in local breed Teleorman Black Head lambs by using carcass and ultrasound measurements of the subcutaneous fat layer thickness, muscle depth, muscle eye area and perimeter of the muscle area of LD muscle.…”
Section: Introductionmentioning
confidence: 99%